2000
DOI: 10.1002/(sici)1097-0215(20000220)90:1<37::aid-ijc5>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three treatment options for single brain metastasis from lung cancer

Abstract: SUMMARY Whole brain radiotherapy (WBRT), stereotactic radiosurgery (SRS), and the combination of both treatment methods were used for the management of single brain metastasis from lung cancer. The purpose of this study is to compare these three different treatment options in terms of local response, survival, and quality of life. From June 1995 to July 1998, 70 lung cancer patients with new diagnosed single brain metastasis were treated with either WBRT alone (n = 29), or SRS alone (n = 23), or the combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2002
2002
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…The type of radiosurgical procedure, gammaknife or Linac-based, does not have an impact on overall survival [18,108]. Radiosurgery, alone or in conjunction with WBRT, has been reported to be superior to conventional WBRT alone in terms of local control, survival and quality of life [72]. This issue is currently being addressed by the RTOG study 9508, which is comparing in a phase III study WBRT with versus without stereotactic radiosurgery boost for patients with single brain metastasis.…”
Section: Stereotactic Radiosurgery (Srs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The type of radiosurgical procedure, gammaknife or Linac-based, does not have an impact on overall survival [18,108]. Radiosurgery, alone or in conjunction with WBRT, has been reported to be superior to conventional WBRT alone in terms of local control, survival and quality of life [72]. This issue is currently being addressed by the RTOG study 9508, which is comparing in a phase III study WBRT with versus without stereotactic radiosurgery boost for patients with single brain metastasis.…”
Section: Stereotactic Radiosurgery (Srs)mentioning
confidence: 99%
“…Some retrospective studies [30,117] and one phase III study from USA [96] have reported that adjuvant WBRT after complete surgical resection significantly reduces local and distant CNS relapses (18 % with surgery + WBRT versus 70 % with surgery alone according to Patchell study), without affecting overall survival or functionally independent survival, except for a modest advantage in patients without evidence of extracranial disease. Similarly WBRT in conjunction with radiosurgery improves local control and reduces the risk of new distant brain metastases [24,47,72,103,116,118],but most studies support the viewpoint that combined radiosurgery and WBRT does not improve the overall survival [44,80,115,118], except for patients without evidence of extracranial disease [98]. WBRT may cause early adverse effects (fatigue, alopecia, eustachian tube dysfunction) and late neurotoxicity.…”
Section: Stereotactic Radiosurgery (Srs)mentioning
confidence: 99%
“…However, the combined therapy did not show a statistically significant advantage over SRS alone in improving survival rates, local control, or the quality of life of patients. Further investigation through randomized trials is needed to assess the value of adding WBRT to SRS in the treatment of patients with single brain metastasis from NSCLC [30]. • SRS provides an effective option in the treatment of patients with metastatic NSCLC.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Another study showed that SRS was superior to WBRT for treating a single brain metastasis. 29 Also, the effectiveness of an SRS boost after WBRT was confirmed by a randomized trial. 30 Most of the results obtained with SRS alone or in combination with other modalities have shown an approximate median survival time of 9 months or more, 29,31,32 which is comparable with, or superior to, that of WBRT or surgery followed by radiation treatment.…”
Section: Supportive Carementioning
confidence: 88%